Improving Students’ Vocabulary Mastery Using the Describing Picture Strategy at MI Miftahul Ulum - Irodatul Muflihah; Budik Kusworo (LP3M KH Yazid Karimullah Institute, 2026)
This study aimed to improve the English vocabulary mastery of sixth-grade students at MI Miftahul Ulum Argotirto through the use of the Describing Picture strategy. Preliminary observations indicated low vocabulary retention and limited student participation due to memorization-oriented learning activities. This research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive model. The findings revealed that the Describing Picture strategy effectively enhanced students’ vocabulary mastery. The percentage of students achieving the minimum score of 75 increased from 43% in Cycle I to 80% in Cycle II. Students were able to understand and use new vocabulary in both oral and written contexts through individual and group picture-description activities. In addition, the strategy improved students’ learning motivation, classroom participation, and self-confidence in using English. Although challenges such as limited instructional time, differences in students’ abilities, and limited availability of visual media were encountered, these issues were addressed through teacher creativity and supportive classroom practices. Overall, the Describing Picture strategy proved to be an engaging, contextual, and effective approach for teaching vocabulary in elementary schools.